(untitled) (Research, Society and Development, 2021)
Objectives: This article intends to demonstrate process of creating a mobile application aimed at the practice of oncology nursing care in order to deepen their knowledge to better serve the person. Information and Communication Technology strategy was chosen in this challenge of creation (by several hands) an application for mobile at the touch of hands, a knowledge search tool for oncology nursing category. Method: Research practice of Participatory Design to raise awareness of professional nurses specializing in oncology was used. Results: It was successful in jointly building an application for the category and concluded that oncology nursing professionals clearly see possibility of educating themselves with the help of digital technologies. Final considerations: It is pointed out that professional-software relationship should be better explored to demystify fear of man x machine and construction of new applications and assimilation of this and many other possibilities.